Analysis Of Teacher Strategies in Promoting Students' Socio-Emotional Development in Inclusive Elementary School Classes - Quratul Thahirah; Syarfuni Syarfuni; Lili Kasmini (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2026)
Inclusive education has become a central paradigm in contemporary educational reform, emphasizing equal learning opportunities for all students regardless of their diverse abilities. However, the implementation of inclusive education in schools often faces pedagogical challenges, particularly in managing classroom diversity and supporting students' socio-emotional development. This study addresses the gap between inclusive education policies and classroom practices by examining how teachers implement strategies to promote students' socio-emotional development in inclusive elementary school classrooms. The purpose of this study was to analyze teachers' pedagogical strategies in promoting students' socio-emotional development in an inclusive environment. This study used a descriptive qualitative approach conducted at SD 44 Banda Aceh, involving the principal, third-grade teachers, and physical education teachers as research participants. Data were collected through in-depth interviews and analyzed using the Miles and Huberman model, including data reduction, data presentation, and conclusion drawing. The findings indicate that socio-emotional development is supported through four main aspects: school policies and institutional support, teachers' understanding of socio-emotional competencies, adaptive teaching strategies in inclusive classrooms, and the integration of socio-emotional values ??into physical education activities. These findings highlight that the development of students' social-emotional skills in inclusive classrooms requires collaborative and systemic support involving school leadership, teacher competency, and an inclusive learning environment.